Možni negativni vplivi prekomerne vlažnosti notranjega okolja v stavbah na zdravje uporabnikov - Kukec, Andreja (Gradbeni vestnik, 2015)
A procedure for failure analysis of reinforced concrete planar beams and frames is presented. It is based on a modified Timoshenko beam finite element. Chosen material models take into account main phenomena of inelastic response of a reinforced concrete frame member: concrete damage by cracking in tension and crushing in compression, and longitudinal steel yielding and failure. Material data needed for the analysis can be obtained either by standardized tests on concrete and steel or from the Eurocodes and other relevant publications. The results of computed examples are presented. They illustrate very satisfying performance of the derived procedure that turned out to be robust and able to nicely describe material failure process in reinforced concrete frames and beams at large load levels.
Keywords: bivalno okolje; Humidity; stavbe; vlažnost; zdravje